Customising fetal weight by ethnicity may ignore confounding with socio-economic status in a UK population. (18th April 2012) - Doyle, S; Johnstone, E; McNamee, R; Sibley, C
Abstract : Introduction: Customised antenatal growth charts (CAGCs) adjust expectations of estimated fetal weight (EFW) based on the assumed effects of maternal characteristics on potential birthweight (Gardosi et al 1992). Previous studies have identified that customisation may be of little actual benefit in the identification of an at-risk fetus (Zhang et al 2007, Hutcheon et al 2008, Zhang et al 2010) and evidence supporting CAGCs use is lacking, particularly in minority ethnic groups. Here, we examine the confounding effects between socio-economic status (SES) and maternal ethnicity in the customisation of birthweight. Methods: Statistical regression analysis was performed on an archive birth record, the Northwest Perinatal Survey (NWPSU), matched via postcode to the English Indices of Deprivation (IMD), an indirect, area-based measure of SES. 194, 548 births from 2004-2008 were studied, and statistical analysis performed using Stata and SPSS software. Additional data was obtained from the Scottish Birth Record (SBR); 238, 314 births from 1999-2010, matched to the Scottish Index of Multiple deprivation (SIMD) were similarly analysed. Results: Statistically significant differences exist in the mean birthweight of all ethnic groups compared with the baseline ethnicity "White" (p<0.001) in NWPSU data. Adjusting for SES results in a decrease in the size of previously observed differences in birthweight by ethnicity. In SBR data, statistically significant differences in mean birthweight exist only in specific minority groups and the size of the ethnic effect varies with the inclusion of SES. Conclusions: This study shows that the inclusion of socio-economic status leads to a variable effect of ethnicity on mean birthweight and potentially to clinically insignificant differences in mean birthweight.